THE EVOLUSION OF THE DERIVATIVE BASE OF VERBS WITH THE PREFIX PRO- IN THE MEANING OF ‘LOSS’ (Proceedings of Southern Federal University. Philology, 2012)
Borovikov A.A.Keywords: verbs with prefix pro-, derivative base, verbal idioms, the cognitive structure, the core meaning, background meanings.The article discusses Russian verbs with prefix pro- meaning ‘loss’ as the result of gambling. The derivative base contains verbal idioms denoting games and gambling activity without direct reference to the situation of loss, which is denoted by the prefix. The first derivatives of that group appeared in the 12th century. In the 17th century other patterns appeared, which are now outdated (izpro-). The cognitive structure seems to be shaped at that period. The amount of pro- verbs denoting ‘loss’ as the result of gambling grows drastically in the 19th century as new base verbs were involved in the word-formation process.